2007
DOI: 10.3324/haematol.11031
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset neutropenia following rituximab results from a hematopoietic lineage competition due to an excessive BAFF-induced B-cell recovery

Abstract: Late-onset neutropenia following rituximab results from a hematopoietic lineage competition due to an excessive BAFF-induced B-cell recoveryRituximab is used in the treatment of lymphoma and autoimmune diseases, for which late-onset neutropenia (LON) were reported. LON-related mechanisms remain unclear. To obtain insights into the mechanisms, we assessed serum, peripheral blood and bone marrow (BM) samples of a patient with LON. Factors classically associated with neutropenia such as anti-neutrophil antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 17 publications
(20 reference statements)
1
47
1
2
Order By: Relevance
“…Maturation arrest at the (pro)myelocyte stage of myelopoiesis is a characteristic feature of severe congenital neutropenia (SCN) of either autosomal dominant or recessive inheritance [15] and is related to mutations in the HAX1 or ELA2 genes [21,22], which in turn is associated with increased myeloid apoptosis at the (pro)myelocyte stage [16,17]. Our current investigations, therefore, provide evidence of similarities in the pathogenesis of LON and SCN.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Maturation arrest at the (pro)myelocyte stage of myelopoiesis is a characteristic feature of severe congenital neutropenia (SCN) of either autosomal dominant or recessive inheritance [15] and is related to mutations in the HAX1 or ELA2 genes [21,22], which in turn is associated with increased myeloid apoptosis at the (pro)myelocyte stage [16,17]. Our current investigations, therefore, provide evidence of similarities in the pathogenesis of LON and SCN.…”
Section: Introductionmentioning
confidence: 58%
“…In further support of this notion, Voog et al [14] identified eight patients with LON and detected antineutrophil antibodies in two of these patients. However, the absence of anti-neutrophil antibodies in other studies [8,10,11,21,22] suggests that additional factors are also involved in LON.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the relationship of late-onset neutropenia to B lymphocyte depletion is intriguing, as patients with late-onset neutropenia had a longer and deeper B lymphocyte depletion and lower serum IgM levels than controls. This phenomenon may be related to a more pronounced B lymphocyte depletion reported in SLE patients with the Fc␥ receptor IIIa 158 V allele after rituximab treatment (10) and to lack of granulopoiesis coinciding with high levels of B lymphocyte-activating factor (11).…”
Section: Discussionmentioning
confidence: 96%
“…One theory is that neutropenia arises from impaired myelopoiesis due to altered growth factors and/or competition between cell lineages in the marrow niche during homeostatic restoration of B cells (Dunleavy et al 2005;Terrier et al 2007). Alternatively, Fas-mediated apoptosis of neutrophils by increased Fas associated with expansion of reactive granular T lymphocytes has been demonstrated by one group (Stamatopoulos et al 2008) but has not been confirmed by other investigators (Fukuno et al 2006;Terrier et al 2007;Tesfa et al 2008).…”
Section: Rituximabmentioning
confidence: 99%